PEREKRUTAN STAFF DEPARTEMENT SALES MARKETING DI HOTEL NOVOTEL PEKANBARU - Fitriana Malida Putri; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Recruitment is the process of selecting and attracting prospective employees who are able to work in a management. So recruitment is an effort to find and attract prospective workers to submit their applications to job vacancies in a company. The purpose of this research is to find out the implementation, constraints and obstacles that occur in the process of recruiting workers at the sales marketing department at Novotel Pekanbaru. This study uses a qualitative method with a descriptive approach to describe the real situation by collecting information data directly from the field. The key informants of this research are the senior sales manager of Novotel Pekanbaru, marketing communication of Novotel Pekanbaru and the TNC department of Novotel Pekanbaru. This study uses data collection techniques from literature study, observation, documentation and interviews. The results of this study can be seen from the recruitment process starting from planning, until the work contract is going well in accordance with the SOP implemented by management and Novotel Pekanbaru, so that employees who are accepted meet the required qualifications. Keywords : Recruitment, Employee, Hotel, Novotel Pekanbaru